THE IMPACT OF ASSESSMENT ON STUDENTS LEARNING - Rustamova Shahnnoza Aripovna; Mamajanova Maftuna Gayrat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
This article represents characterizing assessment settings at the English learning programme level that can distinguish between mixed ability students. In addition, it discusses the elements of effective assessment. In this article, these two methods are used to investigate various levels who learn English as a foreign language. Finally, the relationship between assessment system and student learning responses, as well as assessment environment features that appear to be associated with positive learning responses, are provided.